Incidence and Clinical Impact of Stroke Complicating Transcatheter Aortic Valve Implantation: Results From the German TAVI Registry. Issue 4 (3rd June 2016) - Werner, Nicolas; Zeymer, Uwe; Schneider, Steffen; Bauer, Timm; Gerckens, Ulrich; Linke, Axel; Hamm, Christian; Sievert, Horst; Eggebrecht, Holger; Zahn, Ralf; ,
Abstract : Background: Transcatheter aortic valve implantation (TAVI) has emerged as a safe and effective treatment for patients with severe, symptomatic aortic valve stenosis at high surgical risk over the last years. However, besides its minimal invasive character, TAVI still is an invasive procedure usually performed in a population, carrying a substantial risk for vascular complications, like stroke. Stroke is known to be a rare but serious complication of transvascular interventions in clinical practice, which is associated with high morbidity and mortality rates. Despite broad clinical research in many fields of TAVI over the last years, only sparse data still exist on the incidence and clinical risk factors of stroke complicating TAVI in clinical practice today. Methods: We analyzed data of 1.413 TAVIs, which were enrolled at 30 sites into the prospective and multicenter German TAVI Registry from January 2009 until June 2010. Results: The overall incidence of cerebrovascular events complicating TAVI was 3.2% ( n = 45/1.413) in a real‐world population today. 40% of all cerebrovascular events were classified as transient ischemic attacks (TIA) with symptoms lasting < 24 hr (18/45) and 60% were classified as stroke with symptoms persisting > 24 hr (27/45). All strokes complicating TAVI of 50% were classified as major strokes leading to notable disability in patients, who survive this complication (Modified Ranking Scale 3–6). In‐hospital mortality rate in patients with stroke/TIA was 28.9%, compared to 6.9% in patients without stroke/TIA and 1‐year mortality rate 46.7% versus 18.6%, respectively. In multivariate analysis, prior stroke and renal impairment were found as the only independent predictors for stroke complicating TAVI. Conclusions: Stroke complicating TAVI is a serious complication with a clinically relevant incidence even in daily practice leading to a fivefold increase in 30‐day‐mortality rate, as well as a significant increase in morbidity and disability in patients, who survive this devastating complication. Further research is needed to identify risk factors and ways to reduce stroke after TAVI. © 2016 Wiley Periodicals, Inc.